Clubroot on Oilseed Rape/Canola: A Review - Venkataramana Chapara; PD Meena (Journal of Oilseed Brassica, 2026)
Plasmodiophora brassicae causes the disease clubroot in cruciferous plants, and has been a threat to brassica cropsproduction all over the world since its identification. Clubroot has become a major economically important disease ofoilseed rape (OSR) in many countries, especially in areas where cool, cloudy, and humid weather persists. Further, theimportance of the disease can be determined by its spread in about 88 countries globally on >3700 species of plants, with> 60 vernacular names accountable for 10-100 per cent losses to brassica vegetables, and oil yielding crops. Thepathogen P. brassicae survives in soil as the long time survival structures commonly known as resting spores, and areviable up to 17 years. The resting spores of P. brassicae are highly robust and are well protected by five spore walls.These spore walls are composed of fungal chitin, and carbohydrates that makes the spores resilient to degradation byextra-cellular enzymes produced by predatory soil organisms. Root galls are the characteristics symptoms of the diseaseclubroot, which function as strong metabolic sinks in infected plants by drawing nutrients, and other resources awayfrom the shoots, and leaves contributing to above ground symptoms development. There have been extensiveinvestigations on pathological, physiological, and molecular characteristics of P. brassicae causing clubroot on OSR/canola and over 300 brassica hosts that gives the researchers a scope to work on this pathogen and its managementacross the world. In management of the disease clubroot lack of chemical control option coupled with the need for longercrop rotations forced the deployment of host plant resistance as a major option for clubroot management. Effective andrepeatable controlled-environment and field-screening techniques have been developed for identification of host plantresistance. P. brassicae genome is small in size (24.2-25.5 Mb) with high gene density. The pathogen contains genespotentially involved in host hormone metabolism and metabolic pathways. Mapping of quantitative and qualitativetraits loci (QTL’s) have revealed several (12) dominant loci in B. rapa over 22 QTL’s in B. oleracea and more than 19QTL’s in B. napus for clubroot resistance to different pathotypes of P. brassicae. Eventually several genes governingquantitative and qualitative resistance to P. brassicae have been identified and characterized in different Brassicaspecies. However, some of genes have been demonstrated to be related to the pathogenicity of P. brassicae. Extensiveuse of the resistant cultivars in shorter crop rotations has resulted in emergence of the pathotypes in OSR/canola. Thepathotypes of P. brassicae display great variations with tendencies for overcoming resistance sources from Brassicaspecies in a short period of time. Soil amendments with different types of lime based on pH of the soil were helpful insmall scale applications or in patches. However, the interactions of physical, chemical, and biological, properties betweenP. brassicae, and Brassica hosts and non-hosts in the soil environment are very complex, and pose challenges todetermine conduciveness and suppressiveness of the disease or the pathogen. Integrated disease management (IDM)of clubroot has proved more effective than any of the individual disease management components in large-scale and inon-farm studies conducted in Canada and in the USA. Further information on the biology of P. brassicae and epidemiologyof the disease is needed to strengthen the IDM programs. Current manuscript summarizes on recent studies into the;geographic distribution, morphology, molecular biology, taxonomy, life cycle, symptoms, ecology, host range, geneticbasis of resistance, pathotypes, soil pH, quantification of resting spores from soil and available management practicesof clubroot on OSR/canola have been reviewed with a mention of future research priorities.